MENINGKATKAN KEDISIPLINAN DAN PEMBIASAAN MASYARAKAT DALAM MENGHADAPI NEW NORMAL UNTUK MENCEGAH PENYEBARAN COVID-19 - Lilis Karwati; Ahmad Hamdan; Yus Darusman; Mega Prani Ningsih (IKIP SILIWANGI, 2021)
The current global pandemic disaster requires everyone to always be vigilant in accordance with health protocols. However, in reality there are still many people who lack awareness of the importance of improving discipline and habituation of the community in the face of new normal to prevent the spread of Covid19, the community must have habituation to change behavior to be health conscious. In addition, the pattern of providing health services continues to be improved in addition to the appeal of information either directly or through the media that can provide valuable information to the public about the dangers of the spread of covid 19, during the New Normal period. The target is the gathering place of the community in the pancasila market environment through devotional activities, it is expected to provide increased awareness for the community, provide appeals and direction that can be easily accepted and carried out by the community related to the awareness of Discipline and Habituation of the Community in the face of the pandemic outbreak 19 through a clean lifestyle.